Inequality of bargaining power and the doctrine of unconscionability: Towards substantive fairness in commercial contracts - Alias, Siti Aliza; Abdul Ghadas, Zuhairah Ariff (INSI Publications, 2012)
The issues on unconscionability and inequality of bargaining power are common legal dictums, which are constantly and continuously discussed in consumer contracts. However, the predicaments caused by unconscionability and inequality of bargaining power in commercial contracts are often left side ways despite the alarm, which had been set on by the contractual parties in commercial contracts. Terms on earnest payment, performance bond, pre-determined damages, standard exemption and limitation terms in commercial contracts are examples of practices which arise from the unconscionability and inequality of bargaining power of the contractual parties. This paper looks into the raison de-etre and legal discussion on the principles of unconscionability and inequality of bargaining power under the law of contract and to highlight its application and effect in commercial contracts. References of the discussion are mainly made to the common law principles with occasional reference to the Australian law and Malaysian law. Research methodologies applied in this research are doctrinal and statutory analysis.